Formulasi Sediaan Gel Totol Jerawat Berbahan Aktif Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) Terhadap Bakteri Staphylococcus aureus dan Propionibacterium acnes: Acne Spot Gel Formulation with Active Ingredients Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract Against Staphylococcus aureus and Propionibacterium acnes - Absharina Qisthi Azhari; Dewi Mayasari; Rolan Rusli (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Dragon fruit peel (Hylocereus polyrhizus) has the potential as an antibacterial which can be formulated as an acne spot. Acne spot gel with active ingredients of dragon fruit peel extract was evaluated including olganoleptic, homogeneity, pH, dispersibility and viscosity as well as antibacterial activity against Staphylococcus aureus and Propionibacterium acnes. The results obtained showed that the acne spot gel dragon fruit peel extract was physically stable and had inhibition zones against P. acnes bacteria of 23.855 mm (F1) and 23.671 mm (F2) and against S. aureus bacteria of 22.127 mm (F1) and 23.410. mm (F2).